Potential for Value Chain Improvement and Commercialization of Cape Gooseberry (Physalis peruviana L.) for Livelihood Improvement in Uganda - Barirega, Akankwasah (Ethnobotany Research and Applications, 2014)
Physalis peruviana L., commonly referred to as cape gooseberry, is an important crop for income, food, and medicinal applications. The plant is native to Latin America but has since been naturalized other parts of the tropics. In Uganda, this species grows naturally in abandoned bush fallows. While cape gooseberry has been recently identified as a priority plant for commercialization, little is known about its value chain and potential as a cash, food, and or medicinal plant in Uganda. The objectives of this study were therefore to document and characterize the plant’s value chain, assess its demand and supply, and evaluate the contribution of the plant’s trade to the income of traders in Uganda. Primary and secondary data were collected using a market survey, focus group discussions, field observations, and key informants. A total of 120 value chain actors were interviewed in all the major markets of the city of Kampala, Uganda. The study reveals that the value chain of the plant is short but developing with gatherers/farmers, retailers/petty traders, processors, wholesalers, and consumers being the major stakeholders. Most of the cape gooseberry fruit on the market were coming from the districts of Kabale, Mpigi, and Wakiso, with 85% coming from cultivated gardens and 5% collected from the wild. The cape gooseberry fruit were found to have a high demand on the market, with 67% of the value chain actors rating the demand as high. The average weekly sales for the traders interviewed stood at 49 kg. The supply of the fruit to the market was found to be high as well with 86% of the value chain actors rating supply as high. Supply sustainability rating was significantly positively correlated with economic importance rating of the plant at 99% confidence level (Kendall K = 0.545, P < 0.01, n = 120). The mean value of demand rating was not significantly differently to that of supply at 95% level of significance (P < 0.001). Economic potential of cape gooseberry fruit was found to be high with profit margins of 95% recorded for some cape gooseberry products along the value chain. The government of Uganda ought to promote this plant in a poverty reduction campaign due to its high economic potential.